Dominant-negative loss of function arises from a second, more frequent variant within the SAND domain of autoimmune regulator (AIRE). (March 2018) - Abbott, Jordan K.; Huoh, Yu-San; Reynolds, Paul R.; Yu, Liping; Rewers, Marian; Reddy, Monica; Anderson, Mark S.; Hur, Sun; Gelfand, Erwin W.
Abstract: A genetic variant in the SAND domain of autoimmune regulator (AIRE), R247C, was identified in a patient with type I diabetes mellitus (T1DM) and his mother with rheumatoid arthritis. In vitro, the variant dominantly inhibited AIRE; however, typical features of Autoimmune Polyendocrinopathy Candidiasis and Ectodermal Dysplasia (APECED) were not seen in the subjects. Rather, early manifestation of autoimmunity appeared to be dependent on additional genetic factors. On a population level, diverse variants were identified in this region. Surprisingly, many likely pathogenic variants were seen disproportionately in Africans when compared to Europeans, reinforcing the importance of these variants in altering the immune repertoire. In light of these findings, we propose that R247C and other variants within the SAND-domain alter protein function in a dominant fashion and hold potential as drivers of autoimmunity. Highlights: A novel variant in the SAND domain of AIRE is identified in a family with multiple autoimmune members. The SAND variant dominantly inhibits transactivation of target genes. Variants in the SAND domain are disproportionately present in populations with an African genetic background.